Application of Business Judgement Rule Doctrine in Case Settlement (Case Study of Corruption Crime of PT Asuransi Jiwasraya (Persero)) - Josef Martua Prasetyo Manik (Publikasi Indonesia, 2024)
As is known in Corporate Law, corporate law experts divide 2 (two) major groups of business entity forms, one of which is a legal entity. Included in this group is the Limited Liability Company (PT) The thing that distinguishes between the two types of business entities incorporated and unincorporated lies in the responsibility of the company owner. In relation to practice, business people are more interested in establishing a business entity in the form of a legal entity, namely a Limited Liability Company (